Wearables conquering the workplace of Generation Y: the opportunities and risks to integrate wearable technology at work - Eidenhammer, Lukas (2018)
Purpose - The purpose of this thesis is to investigate the attitude of Generation Y towards Wearable Technology (WT). The investigated gadgets of WT are Fitness trackers, Smart watches, Smart glasses and Smart Clothing. The research investigates the interest of individuals into WT sponsored by the employer and their data-sharing attitude. Design/Methodology - The thesis uses a quantitative, online survey among individuals, which are 18 – 36 years old. The survey is threefold. First, individuals are questioned towards their tracking behavior and ownership of WT. Second, the likelihood to purchase WT is compared with the likelihood to request sponsored WT by an employer. Third, the data-sharing attitude of individuals is investigated. The survey was distributed via Social media and the data gathered via Qualtrics. The analysis was conducted with the statistics program SPSS. Findings - First, the proportion of individuals tracking data and the data tracked confirm the interest of individuals to receive personal insights through WT. Second, the likelihood to request WT when sponsored by an employer shows a statistically significant increase for Smart watches, but decrease for Fitness trackers. For owners of WT, the likelihood increased for all four WTs. Third, the data-sharing attitude of individuals highlighted, that Generation Y does not trust the employer’s objective. Research limitations – The main limitation is that the research is not representative for the whole Generation Y. There exist several definitions of Generation Y and only one definition is applied for this thesis. In addition, the sample was not geographically limited to specific countries. In addition, the survey covers only a limited number of gadgets. Based on the responses for a single gadget, one derives with implications for the whole category of Wearable Technology. In addition, the topic of data sharing is covered by general questions about WT and not retrieved for each of the four devices. Practical implications – By focusing on the individuals’ perspective the thesis provides insight into the attitude of the Generation Y towards the innovative technology of Wearables. The research creates awareness about the employer-employee relationship and the topics of trust and sharing attitude. Employers and companies are interested into the data tracked by individuals and can derive with insights on how to integrate WT at the workplace. Originality – The study focuses on the expectations and concerns of individuals towards WT, in comparison to the numerous studies highlighting the technological features.